Policy Implications for Addressing Roma Precarious Migration Through Employment at Home. (8th March 2013) - Pantea, Maria‐Carmen
Abstract: Roma migration from Romania is often precarious and takes place in circumstances that increase pre‐existent levels of vulnerability. For many, migration is a last resort solution for navigating an insecure economic environment. For others, it has become a source of profit they draw upon, sometimes at the expense of the most vulnerable members of Roma communities. The major challenge this article addresses is how to create the enabling circumstances at home in order to provide alternatives to precarious migration for Roma. Informed by interviews with Roma migrants and with local authorities, this article examines the policy options at local level, addressing Roma precarious migration. It examines the limitations of the current employment policies in relation to Roma in order to identify what seem to work, what sounds promising and what does not work. It advises that job fairs and counselling campaigns are likely to fail, as they do not tackle the structural constraints keeping Roma outside the labour market. Unless linked with realistic employment opportunities, training courses also remain precarious strategies for labour market integration. The article also argues that individualized interventions (including repatriation schemes) are likely to increase community divides. The article supports structural, community‐level measures for tackling unemployment and argues that future policies need to have Roma communities as the 'unit of intervention', because the social preconditions for migration are likely to be generated at this level. This policy proposal is grounded in the research finding that an apparently consistent group of Roma migrants, prone to deceitful recruitment and precarious migration, would endorse reasonable and stable economic solutions at home. Yet accepting that circular migration may be inevitable for a number of Roma is an important ingredient when designing policy interventions.